Adaptação à elevação do nível do mar, pelas mudanças climáticas, nas propriedades privadas na zona costeira brasileira: a possibilidade de aplicação da transferência do direito de construir - Molin, Angela (Universidade do Vale do Rio dos Sinos, 2020)
The proposed research intends to assess the possibility of applying the Transfer of the Right to Build, provided for in the city's statute as a legal instrument to adapt to rising sea level due to climate change in the Brazilian Coastal Zone, for private properties. The importance is to determine the effects of climate change, especially the rise in sea level, property rights, which the Brazilian law has not yet addressed. It can be seen that the legal system or the Law needs to focus on adapting of the Property Law to climate change because the rise in sea level is reality that will not be extinguished overnight, even to cease gas emissions from Planet in the greenhouse. As a result of this situation, the loss of property, or the affected right to build or build on private property, especially in the Brazilian Coastal Zone, is still not current concern in Brazil, despite the disasters that affect the Brazilian coast. The approach begins with the study of the IPCC reports on climate change, focused especially on sea level rise, in addition to the consequences already identified in the field of disaster, and an analysis of how Disasters Law deals with climate change today. In order to contextualize the Coastal Zone, the study points out its characteristics and the legal discipline on this space, within the scope of the federation units, observing the legislation and instruments that the Municipalities, state capitals located on the coast, are using the Coastal Zone management. Finally, in addition to the analysis of the Master Plans of these Municipalities on the adaptation to sea level rise, the study focuses on the Transferable Development Right as a legal instrument to compensate the private owner, whose property is affected by the increase in the level sea. American studies are presented in the research, to support proposals to adapt through the Transferable Development Right as a way to compensate the private owner, and at the end, it concludes by the possibility of its application.
Keywords: Adaptação; Transferência do direito de construir; Zona Costeira; Mudança climática; Adaptation; Transferable development right; Coastal zone; Climate change; ACCNPQ::Ciências Sociais Aplicadas::Direito